Overcoming the ‘Chronic Doubt’: History of Psychology and Argentinian Psychologists’ Training and Education in the Context of Latin-American Psychology - Fierro, Catriel (2018)
The present study presents an empirical analysis of the relevance of psychologists’ historical education within the framework of Latin American psychology. The ‘chronic doubt’ about the formative aim of historiography is first characterized. The ways in which such historiography is a central input in Latin American and Argentinian psychologists’ training and education is then described. The results of a descriptive, mixed socio-bibliometric analysis of the literature used as readings (n = 798) in undergraduate historical courses at Argentinian psychology programs are presented. Findings indicate a marked predominance of texts and scholarship by Argentinian authors, a marked scarcity of Latin American authors and themes, and a problematic depiction of psychology’s historical pluralism. We conclude on the implications of such results for a critical history in the Latin American psychologists’ education, and on the need to contextualize local history in regional history of science.